2013
DOI: 10.1002/chem.201303061
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of Cyclic Tertiary Allylic Alcohols by Asymmetric 1,2‐Addition of AlMe3 to Enones

Abstract: The development of an improved protocol for the enantioselective Rh(I) /binap-catalysed 1,2-addition of AlMe3 to cyclic enones is reported. (31)P NMR analysis of the reaction revealed that the catalyst in its resting state is a chloride-bridged dimer. This insight led to the use of AgBF4 as an additive for in situ activation of the dimeric precatalyst. Thus, the catalyst loading can now be reduced to only 1 mol% with respect to rhodium. Various 5-7-membered cyclic enones can be transformed into tertiary allyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Selective protection of the OOH with TBSCl followed by oxidative cleavage of the vicinal diol and NaBH 4 reduction of the dialdehyde afforded 5 (without any loss of enantiopurity all the way from 2l ). Conversion of 5 into the known triol 6 finally verified the absolute configuration at the C-1 of 2l .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Selective protection of the OOH with TBSCl followed by oxidative cleavage of the vicinal diol and NaBH 4 reduction of the dialdehyde afforded 5 (without any loss of enantiopurity all the way from 2l ). Conversion of 5 into the known triol 6 finally verified the absolute configuration at the C-1 of 2l .…”
Section: Resultsmentioning
confidence: 94%
“…10 min (TLC showed completion of the reaction), concentrated on a rotary evaporator, and purified by column chromatography (1:15 MeOH/CH 2 Cl 2 ) on silica gel to give the known (( S )-2-methylhexane-1,2,6-triol ( 6 ) as a colorless oil (13 mg, 0.088 mmol, 97% from 5 ). Data for 6 : [α] D 25 −3.1 ( c 1.0, EtOAc) (lit . [α] D 20 −2.1 ( c 1.0, EtOAc)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from dialkylzinc, trialkylaluminum was another frequently used reagent in ketone alkylation reactions. In 2013, Zezschwitz and Kolb showed that commercially available AlMe 3 could undergo asymmetric 1,2‐addition reaction to cyclic enones with Rh(I)/( R )‐BINAP 17 as the catalyst (Scheme ) . In this reaction, AgBF 4 was able to activate chloride‐bridged dimeric rhodium catalyst in situ , and thus significantly reduced the catalyst loading to 1 mol% when 1.5 mol% of AgBF 4 was added as the additive.…”
Section: Catalytic Asymmetric Nucleophilic Addition Of Organometallicmentioning
confidence: 99%
“…In view of the need for new efficient strategies for the synthesis of cyclic chiral alcohols, the use of other ortho -functionalized benzaldehydes is described herein, thus expanding the molecular complexity accessible from 2-bromobenzaldehyde, a simple and readily available starting material. Herein, we report the first highly enantioselective allylation of 2-alkynylbenzaldehydes.…”
Section: Introductionmentioning
confidence: 99%